Restorative Justice dalam Tindak Pidana Pembunuhan: Perspektif Hukum Pidana Indonesia dan Hukum Pidana Islam - Sodiqin, Ali (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2015)
The completion of the homicide in Indonesia did’nt have effectiveness, both in order to give a deterrent effect and the creation of the security and peace in society. Conventional punishment process, as applicable in Indonesia, didn’t give space to the parties (the victim, offender, and community ) involved to participate actively in solving their problems. Position of the State was too dominant, thus denying the people's participation in law enforcement. Imprisonment system adopted in Indonesian criminal law also didn’t provide a comprehensive solution. Retributive justice approach adopted by the Indonesian criminal law needs to be reformed and replaced with a restorative justice. Restoration is an alternative approach to solve crime that emphasized on recovery conflicts and rebulid balances in society. This approach has been also applied in many countries, both of which adopted the system of criminal law and civillaw (France, Germany, the Netherlands), or apply the common law system of criminal law (United States, Canada, Australia). This approach is already practiced in Islamic criminal law, namely the law of qisas. In completion of murder, procedure of Qisas involving all parties, namely the victim, offender and community. Family of victim have the right to determine the punishment, whether qisas (killed), or diyat (pay a fine), or give forgiveness to the offender . The existence of three alternative penalties and engagement of the litigants shows that Islamic criminal law applying restorative justice approach. Position of Sultan (the State) is a mediator as well as a supervisor in law enforcement. Completion of this approach is able to resolve crimes with rebuilding relations after the criminal act.